Solid‐Phase Synthesis of Oligonucleotide 5′‐(α‐P‐Thio)triphosphates and 5′‐(α‐P‐Thio)(β, γ‐methylene)triphosphates. Issue 2 (5th December 2014) - Thillier, Yann; Sallamand, Corinne; Baraguey, Carine; Vasseur, Jean‐Jacques; Debart, Françoise
Abstract: A robust solid‐phase synthesis was developed to obtain original oligonucleotides (ONs) functionalized at their 5′ end with modified triphosphate (TP) moieties, in which a nonbridging oxygen atom of the α phosphorus atom was replaced by a sulfur atom and the labile P–O–P linkage was changed into a methylene bridge between the β and γ phosphorus atoms. The efficient method is based on solid‐supported ON assembly followed by 5′‐ H ‐phosphonylation, oxidation to the thiophosphate subsequently activated as a phosphoanhydride with diphenyl phosphoryl chloride, then nucleophilic substitution with the alkylammonium salt of pyrophosphate or its β, γ‐methylene analogue. After deprotection and release from the solid support under basic conditions, 5′‐(α‐ P ‐thio)TP and 5′‐(α‐ P ‐thio)(β, γ‐methylene)TP oligonucleotides were obtained in satisfactory yields, and they were isolated with high purity. These hydrolysis‐resistant 5′‐TP ONs will be useful in biological research to elucidate the mechanism of enzymes involved in mRNA processing and maturation. Abstract : The first synthesis of oligonucleotides (ONs) 5′‐functionalized with a (α‐ P ‐thio)triphosphate moiety is reported. Subsequent ON assembly, 5′‐ H ‐phosphonylation, thiooxidation, activation to phosphoanhydride, and then pyrophosphate or its β, γ‐methylene analogue substitution are achieved on a solid support in good yields. These original hydrolysis‐resistant 5′‐triphosphate ONs will be useful in biological research.